China and Africa : a new paradigm of global business - Kim, Young-Chan (Palgrave Macmillan, 2017)
This book encapsulates the 'New Normal Policy' which has changed the regional policy between China and the African continent. This volume emphasises China's role in Africa as a collaborator in an attempt to fulfil the Beijing consensus in emerging countries. The contextual research encompasses how one can comprehend the influence of the Chinese model in Africa and her diplomatic relations with the continent. China and Africa: A New Paradigm of Global Business endeavours to define whether or not the Washington model has become weathered, and the Beijing consensus more relevant in this specific continent.
Keywords: Economic assistance, Chinese -- Africa.; China -- Relations -- Africa.; Africa -- Relations -- China.; elektronické knihy; electronic books